Rumen fermentation pattern as affected by incorporation of high glucosinolate rapeseed-mustard (Brassica sp.) meal as a protein supplement in sheep - Tripathi, M K; Mishra, A S; Tyagi, A K; Karim, S A; Sharma, S D (The Indian Journal of Animal Sciences, 2012)
Rumen fistulated adult ewes (2) in switch-over design were fed 300g concentrate/day/head with ad lib. ground siris (Albezia lebbeck) pods and baru (Sorghum helipence) hay in 50:50 ratio. Basal 300 g concentrate provided 117 g mustard seed-meal (MSM) which was raised to 160, 200, 250, 300 and 350 g with the addition of pure MSM to study the effect of varying levels of MSM supplementation on rumen fermentation characteristics and thiocyanate (SCN) production. MSM as such contained 5.7% glucosinates. The pH of strained rumen liquor (SRL) ranged from 5.74 to 6.50, averaging 6.12 from 0 to 24 hr post feeding. There was no defined trend in pH changes, whereas, it was higher (P<0.01) at from 0 to 24 hr post feeding. SCN concentration increased linearly (P<0.01) from 0 to 6 hr post feeding, averaging 40.89 Âµg/ml SRL. Total nitrogen was significantly (P<0.05) higher at 2 hr followed by and similar at 4, 6, 8 and 12 hr post feeding, whereas, it was lower in 0 and 24 hr SRL samples. Ammonia nitrogen (NHâ‚ƒ-N), TCA precipitable protein and total volatile fatty acids (TVFA) linearly increased from 0 to 8 hr post feeding followed by declining trends. SCN did not exhibit significant correlation with any of the rumen parameters studied. Whereas it linearly increased with increasing supplementation of MSM (r=0.87). It is concluded that progressive increase in MSM feeding linearly increased the SCN content in SRL, however, its effect on rumen fermentation characteristics was not evident.